Efeito da variação de lítio em catalisadores de ferro tendo potássio e cobre como promotores para a síntese Fischer-Tropsch - Costa, Enio (2010)
New environmental regulations and a possible instability in the international oil market have led to a renewal interest in the Fischer-Tropsch Synthesis (FTS), which is an alternative to produce more environmental friendly fuels. The FTS is a polymerization reaction, in which syngas (H2 + CO) reacts in the presence of catalyst to produce hydrocarbons. Three iron-based catalysts supported in silica and promoted with lithium were synthesized and the effects of lithium content and operating conditions (temperature and pressure) were studied. The composition of the catalysts was based on 100Fe/5Cu/24K/240SiO2 (molar basis) with varying lithium concentration 06Li, 12Li e 24Li. The catalysts were characterized by X-ray fluorescence, X-ray diffraction, thermogravimetric analysis, textural analysis and temperature programming reduction. An experimental planning was carried out for each catalyst, varying the temperature from 240 to 270 ºC and the pressure from 20 to 30 atm. The answer variables were the average carbon number (Nm), dispersion and curtosis of the product distribution. The reactions were carried out in a slurry bed reactor and the products were analyzed by gas chromatography. The products were identified by means of internal standards and quantified by mass balance. The product distribution of the FTS presented a normal distribution in the diesel and wax region. The distribution was similar to a Gaussian curve for all catalysts. The liquid products consisted mainly of n-parafins. The results for all catalysts presented significant quantities of n-parafins in the range of 20 to 36 carbons. The perturbation analysis of the independent variables (temperature, pressure and lithium content) showed that only the lithium content has a significant effect over the average carbon number, at a 90% confidence level. The lithium content presented a negative effect over the average carbon number.